2019
DOI: 10.33545/26164485.2019.v3.i4a.103
|View full text |Cite
|
Sign up to set email alerts
|

Secondary infertility with bilateral cornual block in bicornuate uterus: A case report treated with Homoeopathic medicines

Abstract: Introduction: Bilateral tubal blockage is one of the major causes of infertility by preventing successful passage of the ovum to meet the sperm. Bicornuate uterus is a congenital uterine anomaly often associated with increased rate of spontaneous abortion and infertility. We hereby report a case of secondary infertility with bilateral cornual block in a bicornuate uterus which was under gone hysteroscopic septoplasty by laparoscopic intervention. But after one year continuous Homoeopathic treatment she got pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…10,11 A large number of published studies have shown the efficacy of homoeopathic medicines in the treatment of pathology of female reproductive system that contribute to infertility including cases of polycystic ovarian syndrome, [12][13][14][15][16][17][18] endometriosis, 19 fallopian tubal blockage 19,20 and bilateral corneal block in bicornuate uterus. 21 There is paucity of published literature on efficacy of male factor infertility. A prospective observational pilot study done on male factor infertility (n ¼ 45) has reported the efficacy of individualised homoeopathy on oligoasthenospermia.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 A large number of published studies have shown the efficacy of homoeopathic medicines in the treatment of pathology of female reproductive system that contribute to infertility including cases of polycystic ovarian syndrome, [12][13][14][15][16][17][18] endometriosis, 19 fallopian tubal blockage 19,20 and bilateral corneal block in bicornuate uterus. 21 There is paucity of published literature on efficacy of male factor infertility. A prospective observational pilot study done on male factor infertility (n ¼ 45) has reported the efficacy of individualised homoeopathy on oligoasthenospermia.…”
Section: Discussionmentioning
confidence: 99%
“…Positive pregnancy outcomes have been reported using individualised homoeopathy in cases of female infertility including PCOS, 9 10 11 endometriosis, 12 13 blocked fallopian tubes, 13 bilateral corneal block in bicornuate uterus, 14 secondary infertility with uterine fibroid 15 and male infertility in case of oligoasthenoteratozoospermia associated with necrospermia and hypospermia. 16…”
Section: Previous Studiesmentioning
confidence: 99%